PENERAPAN TARGET COSTING DALAM PENGENDALIAN BIAYA PRODUKSI PADA PT CAHAYA TIMUR GARMINDO - Karisma, Elma; Sedya Utami, Erni Unggul; Karunia, Anita (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2023)
Target Costing is a system that is used to determine the cost of the product as desired as a standard in determining the selling price of the product. This is used so that the company can obtain profits according to the target as well as an effort to control production costs for a product. The purpose of this research is to find out the results of calculating production costs using the target costing method as an effort to control production costs. Data collection techniques used are observation, interviews, library research, and documentation. The data analysist techniques use is quantitative descriptive analysis by going through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the target costing method can be applied to PT Cahaya Timur Garmindo as a means of controlling production costs. By calculating target costing and doing value engineering, the company can save IDR 3,035,485,740. Thus the company is able to achieve the desired profit of 28% of production in the third quarter of 2022. Keywords: target costing, production cost control, production cost